Cruciformity : Paul's narrative spirituality of the cross - Gorman, Michael J., 1955- (Grand Rapids, Mich. : William B Eerdmans Publishing Company., 2001)
"Most studies of Paul concentrate solely on his theology. This book breaks new ground by focusing on the source and nature of Paul's spirituality. Taking his cue from Paul's express desire to "know nothing but Christ crucified," Michael Gorman shows how Paul's personal experience of God constantly intersects with the story of the cross, an event that both reveals the cruciform character of God and shapes believers into a community of "cruciformity" (conformity to the crucified Christ). Expertly combining biblical studies and theological reflection, this noteworthy volume presents a model of the Christian life marked by faith, love, power, and hope." --from book description, Amazon.com
1. The Cruciform God: Paul's Experience of "The Father of Our Lord Jesus Christ" -- 2. The Exalted Crucified Messiah: "Apprehended by Christ to Be Conformed to Him" -- 3. The Spirit of Cruciformity: Paul's Experience of the Spirit of God, the Spirit of Christ -- 4. The Triune God of Cruciform Love: Paul's Experience of the Trinity --
Includes bibliographical references (pages 402-412) and indexes
Keywords: Jesus Christ -- Crucifixion -- Biblical teaching; Bible. -- Theology